EXPERIENCES OF CHILD SEXUAL ABUSE AND CHALLENGES OF DISCLOSURES AMONG JUNIOR SECONDARY SCHOOL STUDENTS IN OGUN STATE, NIGERIA (2023)
Child Sexual Abuse (CSA), which is a form of sexual activity with a minor, is not only a global social problem but also a major risk factor that affects the physical, social and mental well-being of affected children particularly in Nigeria. Previous studies on CSA have largely focused on its causes and prevention among children. However, there is little attention given to the experience, and its disclosure, among students in Junior Secondary Schools (JSS), who are more at risk considering their school-age bracket, (10-17 years), especially in Ogun State. This study was, therefore, designed to investigate the knowledge of, experience, disclosure rate and challenges of disclosure, as well as consequences of, and coping strategies of CSA among JSS students in Ogun State, Nigeria.Ecological Systems Theory provided the framework. A cross-sectional survey design was adopted. Using multi-stage sampling technique, Ogun State was divided into East, Central and West senatorial districts, and 11 Local Government Areas were randomly selected. Stratified purposive sampling was used to select 22 Public JSS. A total sample of 976 respondents was drawn using Lemesho’s (1990) sample size determination formula. Simple random sampling was used to proportionately administer a structured questionnaire to students of JSS consisting of Ogun East (344), Central (325) and West (307). Twelve in-depth interviews were conducted with victims of CSA, and 18 key informant interviews were conducted with School Counsellors (4), Medical Officers (6) and Police Officers (8). Quantitative data were analysed using descriptive statistics, Logistic Regressions and One-way ANOVA at P≤0.05, while the qualitative data were content-analysed.The respondents’ age was 13.18±1.36, 52.2% were male and 61.3% resided in urban centres. Knowledge about CSA was moderately high (50.7%); and significantly associated with students in Junior Secondary (JS) II (OR=1.59), JS III (OR=1.55), male students (OR=0.76) and those who resided in urban centres (OR=1.37). About 30.6% had CSA experiences. The experience of CSA was significantly associated with those who were in JS II (OR=1.41), JS III (OR=1.16), aged 13-15 (OR=1.59), ≥16 years (OR=3.23) and those in urban centres (OR=1.22). The disclosure of CSA rate was low (17.1%); and significantly associated with those who were in JS II(OR=0.18), JS III (OR=0.12), aged 13-15 (OR=2.34), ≥16 years (OR=4.08) and urban residence (OR=1.79). Behavioural disorder (39.1%), re-experiencing (41.2%), anxiety (47.0%), marital dissatisfaction (25.2%) and sexual dysfunction (3.0%) were the consequences of CSA. There were significant differences between age (F(2, 973) =11.87), ethnic group (F(3, 972) =2.455) and the consequences of CSA. Counselling (58.5%), dissociation (7.4%), denial (6.4%) and rationalising (4.0%) were the various coping mechanisms for CSA. The fear of threats, beating, shame, stigmatisation, prosecution of familial perpetrators or offenders and ignorance affected disclosure of CSA among victims and relatives. Experience of CSA resulted in excessive body pains, bruises, unwanted pregnancy and sexually transmitted diseases.The socio-demographic characteristics of Junior Secondary school students influenced the knowledge, experience, disclosure, consequences, and coping strategies of child sexual abuse in Ogun State. These should be factored intoJuniorSecondary school students’ experience and disclosure of child sexual abuse